Survei Tentang Meningkatkan Minat Belajar Siswa SD dalam Pembelajaran PJOK Melalui Permainan Tradisional - Felix Adriano Tarigan Sibero; Samsuddin Siregar; Daniel Sitorus; Cristovel Saragih (Journal of Creative Student Research, 2024)
Physical Education, Sports and Health (PJOK) is an important subject in Elementary School (SD) which aims to improve students' physical, spiritual and social health. However, in reality, many students are less interested in learning PJOK. This is caused by several factors, such as monotonous and less interesting learning methods. This research aims to determine the effectiveness of using traditional games in increasing elementary school students' interest in learning PJOK. The research method used is literature study by examining several literary sources such as journals, scientific articles and books. The research results show that the use of traditional games in PJOK learning can increase elementary school students' interest in learning